The Effects of CLIL Education on the Subject Matter (Mathematics) and the Target Language (English) - Khalid Ouazizi (Universidad de La Sabana, 2016)
This paper investigates the effects of Content and Language Integrated Learning,CLIL for short, on both the attainment of the subject matter, mathematics in ourcase, hence the content aspect of CLIL. The second axes of research focuses on theeffect of CLIL on the learners' proficiency vis-à-vis the language of instruction,epitomized here by English- hence the linguistic aspect of CLIL education. Thispaper adopts a multiple approach methodology to deal with the research questionsat hand. I concluded on the basis of field work, this includes data coding andanalysis, questionnaire design and analysis, an administered mathematical test,and the teacher's continuous assessment of his students, that CLIL education ismore effective than traditional educational systems in helping learners to achievehigh proficiency levels in the target language (English) and to attain high levelsof competence in the subject matter (mathematics). I believe these results mightbe explained by an existing of a covert tradeoff between the brain mechanismsinvolved in learning both mathematics and languages as well as by the pedagogicalopportunities, provided by CLIL environment, and which echo, to a great extent,L1 acquisition environment. doi:10.5294/laclil.2016.9.1.5